1991
DOI: 10.1002/etc.5620100911
|View full text |Cite
|
Sign up to set email alerts
|

Variability in the performance of the seven‐day fathead minnow (pimephales promelas) larval survival and growth test: An intra‐ and interlaboratory study

Abstract: The U.S. Environmental Protection Agency (EPA) has developed a “Seven‐Day Fathead Minnow Larval Survival and Growth Test” for measuring the toxicity of effluents. This study evaluated the ease and performance and the intra‐ and interlaboratory variability of this 7‐d test using two reference toxicants (sodium pentachlorophenate and potassium dichromate), two refinery effluents, and one low‐volume internal waste stream from an electric power plant. Ten different laboratories representing academia, private indus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
14
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 6 publications
3
14
1
Order By: Relevance
“…The representativeness of various species as identified in the present study would also be consistent with Stephan et al (1985) who stated that "results of acute and chronic toxicity tests with representative species of aquatic animals are necessary so that data available for tested species can be considered a useful indication of the sensitivities of appropriate untested species." It has been shown that intralaboratory tests may range up to a factor of twofold for the same species-chemical test combinations (Schimmel 1981;Lemke 1981;DeGraeve et al 1991). In the present study, only five 96-hour LC50s fell below a factor of 0.5 (intralaboratory variation) and three of those were for sturgeon.…”
Section: Discussioncontrasting
confidence: 39%
“…The representativeness of various species as identified in the present study would also be consistent with Stephan et al (1985) who stated that "results of acute and chronic toxicity tests with representative species of aquatic animals are necessary so that data available for tested species can be considered a useful indication of the sensitivities of appropriate untested species." It has been shown that intralaboratory tests may range up to a factor of twofold for the same species-chemical test combinations (Schimmel 1981;Lemke 1981;DeGraeve et al 1991). In the present study, only five 96-hour LC50s fell below a factor of 0.5 (intralaboratory variation) and three of those were for sturgeon.…”
Section: Discussioncontrasting
confidence: 39%
“…The factor of two or five times is statistically based because previous intra-and interlaboratory acute and chronic toxicity test comparisons [21][22][23][24] demonstrated that a twofold difference (i.e., highest to lowest toxicity values) existed for the same species-chemical combinations and methodology for intralaboratory tests. The factor for interlaboratory tests was five times.…”
Section: Resultsmentioning
confidence: 99%
“…Evaluating precision is the primary means of determining the reliability of a toxicity test method for use as a regulatory tool [30]. Toxicity test accuracy cannot be measured, because the response of a test organism cannot be compared to a standard or reference value [25].…”
Section: Discussionmentioning
confidence: 99%